An inducible iFUCCI reporter cell line for tracking cell cycle dynamics in human pluripotent stem cells and their differentiated progeny - Merve Ay; Desi Veleva; Mohammad Chowdhury; Sonja Drljaca; Thais Sobanski; Andrew B.J. Prowse; Dmitry A. Ovchinnikov (Stem Cell Research)
An ability to monitor cell cycle progression in real time has numerous applications in pluripotent stem cell-based models and therapeutics development. Fluorescence Ubiquitination-based Cell Cycle Indicator (FUCCI) systems enable live monitoring of the cell cycle in stem cells and their differentiated progenies in a non-invasive manner. We describe the generation and characterisation of a cell line with a doxycycline-inducible reporter system, iFUCCI, in the human embryonic stem cell (hESC) line MEL-1. MEL-1 iFUCCI hESCs exhibited a normal karyotype, expressed markers of the undifferentiated state, and demonstrated expected differentiation potential by giving rise to cell populations from all three germ layers.